“Ground-Truthing” Efficacy of Biological Control for Aflatoxin Mitigation in Farmers’ Fields in Nigeria: From Field Trials to Commercial Usage, a 10-Year Study - Bandyopadhyay, Ranajit; Atehnkeng, Joseph; Ortega-Beltran, Alejandro; Akande, Adebowale; Falade, Titilayo D. O.; Cotty, Peter J. (Frontiers in Microbiology, 2019)
In sub-Saharan Africa (SSA), diverse fungi belonging to Aspergillus section Flavi frequently contaminate staple crops with aflatoxins. Aflatoxins negatively impact health, income, trade, food security, and development sectors. Aspergillus flavus is the most common causal agent of contamination. However, certain A. flavus genotypes do not produce aflatoxins (i.e., are atoxigenic). An aflatoxin biocontrol technology employing atoxigenic genotypes to limit crop contamination was developed in the US. The technology was adapted and improved for use in maize and groundnut in SSA under the trademark Aflasafe. Nigeria was the first African nation for which an aflatoxin biocontrol product was developed. The current study includes tests to assess biocontrol performance across Nigeria over the past decade. The presented data on efficacy spans years in which a relatively small number of maize and groundnut fields (8 to 51 per year) were treated through use on circa 30,000 ha in commercially-produced maize in 2018. During the testing phase (2009 to 2012), fields treated during one year were not treated in the other years while during commercial usage (2013 to 2019), many fields were treated in multiple years. This is the first report of a large-scale, long-term efficacy study of any biocontrol product developed to date for a field crop. Most (> 95%) of nearly 200,000 tons of maize grains harvested from treated fields contained < 20 ppb total aflatoxins, and a significant proportion (> 90%) contained < 4 ppb total aflatoxins. Grains from treated plots had preponderantly > 80% less aflatoxin content than untreated crops. The frequency of the biocontrol active ingredient atoxigenic genotypes in grains from treated fields was significantly higher than in grains from control fields. A higher proportion of grains from treated fields met various aflatoxin standards compared to grains from untreated fields. Results indicate that efficacy of the biocontrol product in limiting aflatoxin contamination is stable regardless of environment and cropping system. In summary, the biocontrol technology allows farmers across Nigeria to produce safer crops for consumption and increases potential for access to premium markets that require aflatoxin-compliant crops.